Let one odd integer = x
other odd integer = x +2
Sum = x + x+2 = -44
=> 2x + 2 = -44
=> 2x = -44 -2 = -46
=> x = -46/2 = -23
x+2 = -23 + 2 = -21
Integers are -23 and -21
Answer: (x+4)(x^2+16)
Step-by-step explanation:
x^3+4x^2+16x+64
x^3+4x^2+16x+64
=(x+4)(x^2+16)
have a nice day!!
Answer:
it can be factorized. this image gives solution
Answer:
50.264 grams -> 50.2
Step-by-step explanation:
Answer:
n = 245/36
Step-by-step explanation:
Usually, these are solved in 2 steps:
- eliminate fractions by multiplying by the LCM of the denominators
- divide by the coefficient of the variable.
Doing that, we have ...
(49n)(36/49) = (49n)(5/n)
36n = 49·5 = 245 . . . . . simplify
n = 245/36 . . . . . divide by the coefficient of n
_____
Another way to do these is to rewrite the proportion with both sides inverted:
49/36 = n/5
Now, all you need to do is multiply by 5.
n = 5(49/36) = 245/36
__
Or, you can do both of the original steps at the same time:
(49n/36)(36/49) = (49n/36)(5/n)
n = (49·5)/36 = 245/36